Langmuir probe measurements of electron energy probability functions in dusty plasmas. (19th February 2015) - Bilik, N; Anthony, R; Merritt, B A; Aydil, E S; Kortshagen, U R
Abstract: Langmuir probe measurements in dusty plasmas is a challenge because particle and film deposition on the probe leads to contamination and distortion of the current–voltage characteristics. This problem is particularly acute while determining the electron energy probability function (EEPF) from the second derivative of the Langmuir probe current–voltage characteristics. Here, we present reliable EEPF measurements in a capacitively coupled argon–silane dusty plasma using a fast-scanning and shielded Langmuir probe. A solenoid-actuated shield covered the probe and the probe was exposed to the plasma only for short periods of time (less than 6 s) when the current–voltage characteristics were recorded during rapid voltage scans. This approach minimized probe surface contamination. In presence of dust (silicon nanoparticles) the electron density decreased and the electron temperature increased in comparison to a pristine argon plasma. While the population of lower energy electrons decreased in presence of dust, the high energy tail region overlapped throughout the experiment. Langmuir probe measurements were complemented with ion density measurements using a capacitive probe and ex situ examination of particles using electron microscopy.